Composite conductive material and preparation method and application thereof
By using a combination of graphene conductive layer and photosensitive self-healing layer in the heating lens, the problem of easy damage to the conductive layer of the traditional lens is solved, and efficient heating and long-life lenses are achieved, reducing replacement costs.
Patent Information
- Application Number
- CN202411386094.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
AI Technical Summary
The conductive layer of the traditional heating lens is easily damaged during use, resulting in high replacement cost and difficult to effectively extend the service life.
Using composite conductive materials, including graphene conductive layer and photosensitive self-healing layer, the graphene conductive layer activates the benzothiazolene groups and thiol groups in the polymer during damage, forming chemical bonds to repair the conductive layer and extend the lens Service life.
It improves the heating efficiency and infrared transmittance of the lens, extends the service life, reduces the replacement cost, and enhances the chemical stability and corrosion resistance of the lens.
Smart Images

Figure CN119274851A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lens materials, and specifically relates to a composite conductive material and a preparation method and application thereof. Background Art
[0002] With the development of science and technology, near-infrared high-transmittance heated lenses have attracted wide attention in many fields, such as medical devices, smart devices, and military equipment, due to their unique functions and properties. However, as the use time of traditional heated lenses increases, the conductive layer is easily damaged during use, and the replacement cost is high. Summary of the invention
[0003] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a composite conductive material, which is used for near-infrared high-transmittance heating lenses, has a conductive layer with photosensitivity self-repairing ability, and has good application prospects.
[0004] The invention also provides a method for preparing the composite conductive material.
[0005] The invention also proposes a near-infrared high-transmittance heating lens.
[0006] The invention also proposes a method for preparing a near-infrared high-transmittance heating lens.
[0007] The present invention also proposes the application of the composite conductive material or near-infrared high-transmittance heating lens.
[0008] In a first aspect of the present invention, a composite conductive material is proposed, comprising a near-infrared transparent substrate and a graphene conductive layer disposed on the surface of the substrate, wherein the surface of the graphene conductive layer is provided with a photosensitive self-repairing layer capable of repairing the conductive layer.
[0009] The composite conductive material according to the embodiment of the present invention has at least the following beneficial effects:
[0010] As an emerging two-dimensional carbon nanomaterial, graphene has excellent mechanical properties, such as high Young's modulus and fracture strength, good electrical and thermal conductivity, excellent optical properties, good chemical stability and corrosion resistance. Graphene is used as a conductive material in composite conductive materials. It is used in near-infrared high-transmittance heating lenses (also called near-infrared high-transmittance heating and defogger lenses), which not only improves the heating efficiency and infrared transmittance of the lenses, but also due to the setting of the photosensitive self-repairing layer, when the graphene conductive layer is damaged (defective or broken), it releases chemicals or triggers chemical reactions under the irradiation of light to fill or repair the cracks or defects of the graphene conductive layer, thereby restoring the conductive properties and increasing the service life of the lenses. It has good application prospects.
[0011] In some embodiments of the present invention, the photosensitive self-healing layer includes a conjugated polymer containing a benzothiazolone group and a thiol group.
[0012] Through the above-mentioned embodiment, the composite conductive material is placed under ultraviolet light of appropriate wavelength for irradiation. Appropriate wavelength can activate the photosensitivity of benzothiazolone group and thiol group in polymer. Under the action of light, benzothiazolone group can undergo cyclization or ring-opening reaction, thereby chemically interacting with graphene surface and improving the conductivity of conductive film. Thiol group can form bond with graphene surface through photoinduced sulfurization reaction or free radical reaction, further enhance the repair effect and durability, so that the conductive layer has photosensitive self-repairing function after being damaged. In some embodiments of the present invention, 2-hydroxybenzothiazole (C7H5NOS) etc. can be selected as raw material, connected to the chain of polymer by nucleophilic substitution and the like, to obtain polymer with benzothiazolone group.
[0013] In some embodiments of the present invention, the graphene conductive layer can be repaired by irradiating the composite conductive material under ultraviolet light with a wavelength of 280 to 380 nm.
[0014] In some embodiments of the present invention, the conjugated polymer includes a main chain containing a poly(3-alkylthiophene) group, and further includes a side chain containing a benzothiazolone group and a side chain containing a thiol group.
[0015] Through the above-mentioned embodiments, poly(3-alkylthiophene) is a class of conjugated polymers with specific structures and properties. Due to its conjugated structure and charge transport properties, it has high conductivity and is particularly suitable for preparing conductive polymer films and devices; through appropriate functionalization and side chain modification, poly(3-alkylthiophene) can adjust solubility, so that it is easy to handle and process in solution; and it is usually flexible and elastic, which makes them perform well in certain applications such as flexible electronic devices; this type of polymer usually has good chemical stability and can work stably for a long time under certain environmental conditions. Poly(3-alkylthiophene) is a polythiophene derivative with good conductivity and photosensitivity. It can undergo photoinduced reaction under light, which helps to repair or enhance the conductivity of the conductive layer, making it have a wide range of application potential in optoelectronic devices, sensors and flexible electronic technology.
[0016] The present invention adopts a poly (3-alkylthiophene) derivative having a side chain of a benzothiazolone group and a side chain of a thiol group, and these side chains can undergo a photoinduced reaction under illumination conditions. The benzothiazolone group can generate an excited state or a free radical under illumination, and these reactive intermediates can chemically react with the surface functional groups of graphene to form chemical bonds or crosslinks. That is, the photosensitive nature of the benzothiazolone group enables it to chemically react with the graphene surface under illumination to enhance conductivity. The thiol group enhances the combination and stability of the repair layer and graphene through photoinduced sulfurization or free radical reaction.
[0017] In some embodiments of the present invention, the raw materials for preparing the photosensitive self-repairing layer include a main chain raw material and benzothiazolyl acid, and the main chain raw material includes 3-alkylthiophene or poly (3-alkylthiophene).
[0018] In some embodiments of the present invention, the raw materials for preparing the photosensitive self-repairing layer also include mercaptoethanol.
[0019] In some embodiments of the present invention, the thickness of the photosensitive self-healing layer is 100-300 nm.
[0020] In some embodiments of the present invention, the thickness of the near-infrared transparent substrate is 120-250 μm.
[0021] In some embodiments of the present invention, the near-infrared transparent substrate includes at least one of near-infrared transparent glass and polymer I. Optionally, the near-infrared transparent glass is a glass with high near-infrared transmittance.
[0022] In some embodiments of the present invention, the polymer I comprises at least one of polycarbonate, polyethylene terephthalate, polyethylene naphthalate, polyimide or polymethyl methacrylate.
[0023] In some embodiments of the present invention, the transmittance of near infrared light in the near infrared transparent substrate is 90-96%.
[0024] In some embodiments of the present invention, the wavelength of the near-infrared light is 800-1000 nm.
[0025] In some embodiments of the present invention, the transmittance of visible light in the near-infrared light-transmitting substrate is less than 10%.
[0026] In some embodiments of the present invention, the graphene conductive layer is prepared by chemical vapor deposition, solvent stripping or oxidation-reduction method, preferably chemical vapor deposition (CVD).
[0027] The preparation of graphene by CVD method can meet the needs of large-scale production and is more meaningful for commercial applications; graphene prepared by CVD method has higher crystallinity and lower defect density, which means that its electrical, optical and thermal properties are better and can meet the needs of various high-performance applications; CVD method can precisely control the growth process, and optionally adjust the number of graphene layers, crystal structure and morphology by adjusting the production environment (temperature, time, carbon source flow, gas environment).
[0028] In the present invention, graphene is used as a conductive material. The graphene prepared by the CVD method has excellent properties such as high conductivity, high light transmittance, and high stability, which greatly improves the heating efficiency of the lens and ensures high transmittance of near-infrared light.
[0029] In some embodiments of the present invention, the thickness of the graphene conductive layer is 0.5-5 nm.
[0030] In some embodiments of the present invention, the composite conductive material includes a near-infrared light-transmitting substrate, a graphene conductive layer, and a photosensitive self-healing layer which are stacked in sequence.
[0031] In some embodiments of the present invention, the composite conductive material further includes an electrode sheet, and the electrode sheet is electrically connected to the graphene conductive layer.
[0032] In some embodiments of the present invention, an electrode sheet is disposed at the edge of the graphene conductive layer. Optionally, an electrode sheet is disposed at both ends of the graphene conductive layer.
[0033] In some embodiments of the present invention, an electrode sheet is provided on an edge of the graphene conductive layer away from the substrate.
[0034] In some embodiments of the present invention, the area of the electrode sheet on the surface of the graphene conductive layer accounts for 2-6%.
[0035] In some embodiments of the present invention, the composite conductive material further includes an overheat protection switch.
[0036] In some embodiments of the present invention, the overheat protection switch is disposed on a side of the graphene conductive layer away from the near-infrared transparent substrate.
[0037] In some embodiments of the present invention, the near-infrared high-transmittance heating lens further includes a packaging insulating layer, and the packaging insulating layer is located on a side of the photosensitive self-repairing layer away from the graphene conductive layer.
[0038] In some embodiments of the present invention, the graphene conductive layer and the electrode sheet are both located between the encapsulation insulating layer and the near-infrared transparent substrate. The encapsulation insulating layer can improve the environmental stability and durability of the lens and optimize the performance of the heating device. Optionally, the overheat protection switch is located between the encapsulation insulating layer and the near-infrared transparent substrate; or, the encapsulation insulating layer is located between the overheat protection switch and the near-infrared transparent substrate.
[0039] In some embodiments of the present invention, the overheat protection switch is arranged on a side of the packaging insulation layer away from the photosensitive self-repairing layer.
[0040] In some embodiments of the present invention, the composite conductive material includes a transparent area and a non-transparent area, and an overheat protection switch and an electrode sheet are arranged in the non-transparent area.
[0041] In some embodiments of the present invention, the transmittance of visible light in the transparent region of the composite conductive material is less than 5%.
[0042] In some embodiments of the present invention, the transmittance of near infrared light in the transparent region of the composite conductive material is 86-96%. Optionally, the wavelength of the near infrared light is 800-1000 nm.
[0043] The second aspect of the present invention provides a method for preparing a composite conductive material, comprising the following steps:
[0044] S1, preparing a graphene conductive layer;
[0045] S2, compounding the graphene conductive layer with a near-infrared transparent substrate to obtain a material intermediate;
[0046] S3, preparing a photosensitive self-healing layer on the side of the graphene conductive layer away from the near-infrared transparent substrate to obtain the composite conductive material.
[0047] In some embodiments of the present invention, in step S1, a graphene conductive layer is prepared by chemical vapor deposition.
[0048] In some embodiments of the present invention, step S1 includes the following operations:
[0049] S1-1, pre-treating the substrate, wherein the pre-treatment includes cleaning, polishing and annealing steps;
[0050] S1-2, preparing a graphene conductive layer on the pretreated substrate surface by chemical vapor deposition.
[0051] In some embodiments of the present invention, the substrate includes a metal substrate, such as a copper-nickel alloy substrate, a copper substrate, a nickel substrate, etc.
[0052] In some embodiments of the present invention, step S1-1 includes the following operations:
[0053] S1-1-1, cleaning the substrate with a cleaning agent, and then washing with water to obtain a cleaned substrate; the cleaning agent includes at least one of ethanol or acetone;
[0054] S1-1-2, connecting the cleaned substrate to a chemical workstation for polishing, then washing with water, and drying to obtain a polished substrate;
[0055] S1-1-3, annealing the substrate obtained in S1-1-2 at 1000-1200° C. for 1-6 hours to obtain a pretreated substrate.
[0056] Use ethanol and acetone to clean the substrate to remove oil and impurities on the substrate surface, then rinse with water (such as deionized water) to remove residual cleaning agent. Polishing pretreatment to ensure the flatness and cleanliness of the substrate surface; annealing treatment to eliminate residual stress and lattice defects in the substrate and improve the growth quality of graphene.
[0057] In some embodiments of the present invention, in step S1-1-2, the polishing liquid used in the polishing step includes a mixture of polyethylene glycol and phosphoric acid. Optionally, the volume ratio of polyethylene glycol to phosphoric acid is (3-6):1.
[0058] In some embodiments of the present invention, in step S1-2, in the chemical vapor deposition step, the graphene conductive layer is obtained by chemical deposition of the reaction gas, wherein the reaction gas used includes methane and hydrogen. Optionally, the volume ratio of methane to hydrogen is 1:(5-10).
[0059] In some embodiments of the present invention, in step S1-2, in the chemical vapor deposition step, the gas flow rate of the reaction gas is 100 to 300 sccm.
[0060] In some embodiments of the present invention, in step S1-2, in the chemical vapor deposition step, the reaction pressure is no higher than 0.02 MPa, wherein the reaction pressure refers to the pressure in the reaction chamber where the chemical vapor deposition occurs.
[0061] In some embodiments of the present invention, in step S1-2, the vapor deposition temperature in the chemical vapor deposition step is 1000-1200° C., and the deposition time is 1-6 hours.
[0062] In some embodiments of the present invention, step S1-2 includes the following operations:
[0063] S1-2-1, introducing a reaction gas containing methane and hydrogen into the reaction chamber, the gas flow rate of the reaction gas is 100 to 300 sccm, the gas pressure in the reaction chamber is not higher than 0.02 MPa, wherein the volume ratio of methane to hydrogen is 1:(5 to 10);
[0064] S1-2-2, heating the reaction gas to 1000-1200° C. to cause a chemical vapor deposition reaction, the reaction duration is 0.5-2 hours, and the graphene conductive layer is formed.
[0065] Optionally, after the graphene conductive layer is grown, the reaction chamber can be slowly cooled to room temperature to prevent the graphene conductive layer from cracking or peeling due to a sudden drop in temperature. Optionally, nitrogen gas is continuously introduced as a protective gas to maintain a stable pressure in the chamber, so that the graphene is less susceptible to oxidation.
[0066] In some embodiments of the present invention, step S2 includes the following operations: using a transfer medium polymethyl methacrylate (PMMA) to apply to the graphene conductive layer obtained in step S1, etching the substrate with an etching solution, cleaning the graphene conductive layer, and then compounding with a near-infrared light-transmitting substrate, washing away the transfer medium, and obtaining a composite conductive material. Optionally, the compounding method is lamination.
[0067] In some embodiments of the present invention, the etching solution includes an ammonium sulfate solution, such as an ammonium sulfate aqueous solution.
[0068] In some embodiments of the present invention, acetone is used to wash away the transfer medium in step S2.
[0069] In some embodiments of the present invention, step S3 further includes the step of preparing an electrode sheet;
[0070] In some embodiments of the present invention, the step of preparing the electrode sheet specifically comprises the following steps:
[0071] In some embodiments of the present invention, an electrode sheet is prepared on the surface of the graphene conductive layer or the surface of the photosensitive self-healing layer by screen printing.
[0072] In some embodiments of the present invention, 200-mesh screen-printed silver paste electrodes are formed on both ends of the surface of the graphene conductive layer or the photosensitive self-healing layer, and dried at 80-150° C. for 0.5-3 h to obtain the electrode sheet.
[0073] In some embodiments of the present invention, the thickness of the electrode sheet is 15 to 30 μm.
[0074] In some embodiments of the present invention, step S3 comprises the following steps:
[0075] S3-1, preparing a repair solution containing a poly(3-alkylthiophene) derivative, specifically comprising: polymerizing a 3-alkylthiophene monomer to form a main chain of a poly(3-alkylthiophene), using benzothiazolone acid to connect a benzothiazolone group to a side chain of the poly(3-alkylthiophene) through nucleophilic substitution, and then reacting with mercaptoethanol to introduce a thiol group into the side chain to obtain a poly(3-alkylthiophene) derivative, and then mixing with a solvent to obtain the repair solution;
[0076] S3-2, coating the repair solution on the surface of the graphene conductive layer and drying it to form the photosensitive self-repairing layer.
[0077] In some embodiments of the present invention, in step S3-1, the solvent includes ethyl acetate.
[0078] In some embodiments of the present invention, step S3-1 specifically includes:
[0079] S3-1-1, mixing 3-alkylthiophene with chloroform to obtain a 3-alkylthiophene chloroform solution;
[0080] S3-1-2, mixing a chloroform solution of 3-alkylthiophene with an aqueous solution of FeCl3 (concentration of 0.1 mol / L), and reacting the mixture to obtain a benzothiazole keto acid;
[0081] S3-1-3, mixing a benzothiazolone acid dichloromethane solution with poly(3-alkylthiophene), adding an alkaline catalyst aqueous solution, reacting to obtain a benzothiazolone group-containing poly(3-alkylthiophene);
[0082] S3-1-4, dissolving the poly(3-alkylthiophene) containing benzothiazolone group in ethyl acetate to obtain solution I, adding the mercaptoethanol aqueous solution to solution I to cause a nucleophilic substitution reaction, and after the reaction is completed, precipitating to obtain product I; wherein product I is the product of the side chain of poly(3-alkylthiophene) connected to the thiol group of the benzothiazolone group.
[0083] S3-1-5, dissolving product I in ethyl acetate to obtain a coating solution, coating the coating solution on the surface of the graphene conductive film, and drying to obtain a composite conductive material.
[0084] In step S3-1-1, the concentration of 3-alkylthiophene in the 3-alkylthiophene chloroform solution is 0.1 to 2 mol / L
[0085] In step S3-1-2, the volume ratio of the 3-alkylthiophene chloroform solution to the FeCl3 aqueous solution is 5:(1 to 5).
[0086] In step S3-1-2, the reaction temperature is 70 to 90° C., and the reaction time is 5 to 20 hours.
[0087] In step S3-1-2, ethanol can be added to the reaction system to terminate the reaction. Optionally, the amount of ethanol added is 2 times the total volume of the reaction solution. Ethanol, as a reducing agent, can react with FeCl3 to reduce the oxidizing ability of FeCl3, thereby terminating the oxidative polymerization reaction of 3-alkylthiophene. FeCl3 acts as a strong oxidant in the reaction. Ethanol reduces FeCl3 to reduce its oxidizing ability, thereby achieving the effect of terminating the reaction.
[0088] In step S3-1-3, benzothiazolidone acid is dissolved in dichloromethane to obtain a benzothiazolidone acid dichloromethane solution. Optionally, the concentration of benzothiazolidone acid in the benzothiazolidone acid dichloromethane solution is 0.01 to 0.5 mol / L.
[0089] In step S3-1-3, the volume ratio of the benzothiazolyl acid dichloromethane solution to the poly(3-alkylthiophene) is (0.5-5):1.
[0090] In step S3-1-3, the alkaline catalyst aqueous solution includes a NaOH aqueous solution. Optionally, the concentration of the catalyst in the alkaline catalyst aqueous solution is 0.1 to 2 mol / L.
[0091] In step S3-1-3, the volume ratio of the benzothiazolyl acid dichloromethane solution to the poly(3-alkylthiophene) and the alkaline catalyst aqueous solution is (8-12):(8-12):1.
[0092] In step S3-1-3, the reaction temperature is 50-70°C and the reaction time is 8-15h.
[0093] In step S3-1-3, after the reaction is completed, the product is washed with ethanol and precipitated to obtain a poly(3-alkylthiophene) containing a benzothiazolone group.
[0094] In step S3-1-4, the concentration of the poly(3-alkylthiophene) having benzothiazolone groups in solution I is 2 to 8 mg / mL.
[0095] In step S3-1-4, the concentration of mercaptoethanol in the mercaptoethanol aqueous solution is 0.01 to 0.2 mol / L.
[0096] In step S3-1-4, the volume ratio of the mercaptoethanol aqueous solution to solution I is 1:(8-12).
[0097] In step S3-1-4, the temperature of the nucleophilic substitution reaction is 40 to 60° C., and the reaction time is 1 to 10 hours.
[0098] In step S3-1-5, the concentration of product I in the coating solution is 1 to 5 mg / mL.
[0099] In step S3-1-5, the drying temperature is 70 to 90°C and the drying time is 0.5 to 10 hours.
[0100] In some embodiments of the present invention, in step S3-2, the drying temperature is 60 to 90°C, and the drying time is 0.5 to 3 hours.
[0101] In some embodiments of the present invention, in step S3-2, the coating method includes but is not limited to spraying, spin coating, scraping, etc.
[0102] In some embodiments of the present invention, the preparation method further includes step S4, preparing a packaging insulation layer and setting an overheat protection switch.
[0103] The third aspect of the present invention provides a near-infrared high-transmittance heating lens, comprising the above-mentioned composite conductive material.
[0104] In some embodiments of the present invention, the lens of the present invention is a near-infrared high-transmittance heated defog lens.
[0105] In some embodiments of the present invention, the transmittance of near infrared light in the near infrared high transmittance heating lens is 86-96%. Optionally, the wavelength of the near infrared light is 800-1000nm.
[0106] In some embodiments of the present invention, the transmittance of visible light in the near-infrared high-transmittance heated lens is less than 10%.
[0107] A fourth aspect of the present invention provides a method for preparing a near-infrared high-transmittance heated lens, comprising the following steps:
[0108] S1, preparing a graphene conductive layer;
[0109] S2, compounding the graphene conductive layer with a near-infrared transparent substrate to obtain a material intermediate;
[0110] S3, preparing a photosensitive self-healing layer on a side of the graphene conductive layer away from the near-infrared transparent substrate.
[0111] In some embodiments of the present invention, the preparation method further includes step S4, preparing a packaging insulation layer and setting an overheat protection switch.
[0112] In a fifth aspect of the present invention, the application of the composite conductive material or near-infrared high-transmittance heated lens in night vision equipment or security monitoring equipment is proposed. By using the composite conductive material or near-infrared high-transmittance heated lens in the equipment, the composite conductive material or near-infrared high-transmittance heated lens can be heated during use of the equipment to heat and remove water mist.
[0113] In a sixth aspect of the present invention, a near-infrared night vision device is proposed, comprising the above-mentioned composite conductive material or near-infrared high-transmittance heated lens.
[0114] In a seventh aspect of the present invention, a near-infrared security monitoring lens is provided, comprising the above-mentioned composite conductive material or near-infrared high-transmittance heating lens. BRIEF DESCRIPTION OF THE DRAWINGS
[0115] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0116] Figure 1 This is a schematic diagram of the structure of the near-infrared high-transmittance heating lens in Example 1 of the present invention;
[0117] Figure 2 It is a schematic diagram of the temperature test by the 9-point test method in the test example of the present invention;
[0118] Figure 3 This is a diagram showing the effect of the near-infrared high-transmittance heating lens after heating in Example 1 of the present invention.
[0119] Figure numerals: 1. packaging insulation layer; 2. electrode sheet; 3. overheat protection switch; 4. graphene conductive layer + self-healing layer; 5. near-infrared transparent substrate. DETAILED DESCRIPTION
[0120] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0121] The experimental methods without specific conditions in the following examples and comparative examples are generally based on conventional conditions in the art or conditions recommended by the manufacturers; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents available from commercial channels such as conventional markets.
[0122] Polyethylene glycol 200, CAS No. 25322-68-3, AR, 500mL, Sinopharm Reagent;
[0123] Polymethyl methacrylate, CAS No. 9011-14-7, MW35000, 100g, Sinopharm Reagent;
[0124] Phosphoric acid, CAS No. 7664-38-2, GR, ≥85%, 500ml, Sinopharm Reagent;
[0125] Ammonium sulfate, CAS No. 7783-20-2, AR, ≥99.0%, 250g, Sinopharm Reagent;
[0126] 3-Alkylthiophene monomer, CAS No. 104934-52-3, 98%, 5g, Sinopharm Reagent;
[0127] Benzothiazole keto acid is prepared by a method comprising the following steps: mixing a benzothiazole solution having a concentration of 0.5 mol / L and a chloroacetic acid solution having a concentration of 0.6 mol / L in a volume ratio of 1:1, reacting under alkaline conditions (pH of 13, sodium hydroxide can be used to adjust the pH), the reaction temperature is 70° C. (reaction time is 5 h), and benzothiazole keto acid is prepared. The solvent in the benzothiazole solution and the chloroacetic acid solution can both be ethanol.
[0128] Chloroacetic acid, CAS No.: 79-11-8, AR, ≥98%, 100g, Sinopharm Reagent;
[0129] Benzothiazole, CAS No.: 95-16-9, AR, ≥ 99.0%, 100g, Sinopharm Reagent;
[0130] Mercaptoethanol, CAS No. 60-24-2, CP, 500mL, Sinopharm Reagent;
[0131] Sodium hydroxide, CAS No. 1310-73-2, AR, > 96%, 500g, Sinopharm Reagent;
[0132] Ferric chloride, CAS No. 7705-08-0, CP, ≥97%, 500g, Sinopharm Reagent;
[0133] Ethyl acetate, CAS No. 141-78-6, AR, ≥99.5%, 500mL, Sinopharm Reagent;
[0134] Ethanol, CAS No. 64-17-5, AR, ≥95%, 500mL, Sinopharm Reagent;
[0135] Acetone, CAS No. 67-64-1, AR, ≥99.5%, Sinopharm Reagent;
[0136] Dichloromethane, CAS No. 75-09-2, AR, ≥99.5%, Sinopharm Reagent;
[0137] Copper-nickel alloy substrate: B0.6 copper-nickel alloy, copper mass percentage ≥ 99.3%, nickel mass percentage = 0.6%, t (thickness) = 20 μm, Shanghai Muran Industrial Development Co., Ltd.;
[0138] Copper substrate, CAS No. 7440-50-8, ≥99.99%, t (thickness) = 20 μm, Sinopharm reagent;
[0139] Nickel substrate, CAS No. 7440-02-0, ≥99.99%, t (thickness) = 20 μm, Sinopharm reagent;
[0140] Example 1
[0141] This embodiment discloses a composite conductive material, the preparation process of which includes the following steps:
[0142] (I) Substrate preparation: Select a metal copper-nickel alloy substrate, clean the copper-nickel alloy substrate with a cleaning agent (the cleaning agent is ethanol or acetone) to remove oil and impurities on the surface, and then rinse it with deionized water to remove the residual cleaning agent. Next, use a polishing liquid (a mixture of polyethylene glycol and phosphoric acid, the volume ratio of polyethylene glycol and phosphoric acid in the mixture is 5:1), connect the copper-nickel alloy substrate to the chemical workstation for polishing, polish pretreatment to ensure the flatness and cleanliness of the substrate surface, and then rinse it with deionized water. Among them, the polishing conditions are: at room temperature of 25°C, the speed of the polishing liquid flowing through the substrate is 30sccm, the time is 8min, the stirring speed of the polishing liquid is 100RPM, the pressure applied by the polishing liquid on the substrate is 0.1bar, and the pH value of the polishing liquid is 2.
[0143] The polished copper-nickel alloy substrate is placed in a drying oven to dry and remove surface moisture. The dried copper-nickel alloy substrate is placed in a high-temperature annealing furnace under an argon atmosphere at 1000°C for 2 hours for annealing to eliminate residual stress and lattice defects in the copper-nickel alloy substrate and improve the growth quality of graphene.
[0144] (II) Introduction of reaction gases: methane and hydrogen are introduced into the quartz tube of the reaction chamber at a volume flow ratio of 1:10, with a total gas flow rate of 200 sccm and a gas pressure in the quartz tube not higher than 0.02 MPa.
[0145] (III) High temperature treatment: The reaction chamber is heated to 1200°C, and methane is fully decomposed into carbon atoms and hydrogen atoms. The carbon atoms are attached to the copper-nickel alloy substrate. The carbon atoms attached to the substrate are arranged according to the lattice structure of graphene to form a continuous graphene film. The reaction lasts for 3 hours.
[0146] (IV) Cooling treatment: After the graphene film is grown, the reaction chamber is slowly cooled to room temperature to prevent the graphene film from cracking or peeling due to a sudden drop in temperature. It is necessary to continue to introduce protective gas nitrogen to maintain a stable pressure in the chamber to prevent the graphene from being oxidized.
[0147] (V) Graphene film transfer: Use transfer medium polymethyl methacrylate (PMMA) to coat the graphene film, put it into an ammonium sulfate aqueous solution with a concentration of 0.5 mol / L for etching (the graphene film can be completely immersed in the ammonium sulfate aqueous solvent), and remove the copper-nickel alloy substrate (etch until the copper-nickel alloy substrate is completely dissolved, the time is about 3 hours). After the copper-nickel alloy substrate is removed, it is washed with deionized water to obtain a high-quality graphene film (thickness of 2nm, graphene conductive layer). The graphene film is directly contacted and bonded with a near-infrared transparent substrate, and then acetone is used to remove PMMA to obtain a conductive intermediate material. Among them, the near-infrared transparent substrate is a near-infrared highly transparent substrate (thickness of 180μm) that is not transparent to visible light, and is specifically selected from polycarbonate (the transmittance of visible light in the substrate is 5% to 6%; the transmittance of near-infrared light with a wavelength of 800 to 1000nm in the substrate: 96%).
[0148] (VI) Preparation of self-healing layer: prepare a repair solution containing a poly(3-alkylthiophene) derivative. Use 3-alkylthiophene monomer to polymerize to form the main chain of poly(3-alkylthiophene), benzothiazole acid uses nucleophilic substitution to connect the benzothiazole group to the side chain of poly(3-alkylthiophene), use mercaptoethanol to react with poly(3-alkylthiophene), and use the thiol group to undergo a nucleophilic substitution reaction with the active site on the polymer side chain, thereby introducing the thiol group into the side chain. The side chain of poly(3-alkylthiophene) is connected to the benzothiazole group and the thiol group and then dissolved in an ethyl acetate solution. Coat (spray, spin coat, scrape, etc.) the polymer ethyl acetate solution on the surface of the graphene conductive layer (leave a blank area for preparing electrode sheets at both ends of the graphene conductive film surface), ensure uniform coverage and full contact with the graphene conductive layer, and dry. Specifically, it includes the following steps:
[0149] 3-Alkylthiophene monomer was dissolved in chloroform with a concentration of 0.5 mol / L to obtain 3-alkylthiophene chloroform solution, and a catalyst FeCl3 aqueous solution (concentration of 0.1 mol / L) was added, and the volume ratio of 3-alkylthiophene chloroform solution to FeCl3 aqueous solution was 5:2. The reaction was carried out at a temperature of 80°C for 10 hours, and ethanol was added to terminate the reaction (the amount of ethanol added was twice the total volume of the above reaction solution. Ethanol, as a reducing agent, can react with FeCl3 to reduce the oxidizing ability of FeCl3, thereby terminating the oxidative polymerization reaction of 3-alkylthiophene. FeCl3 acts as a strong oxidant in the reaction. Ethanol reduces FeCl3 and reduces its oxidizing ability, thereby achieving the effect of terminating the reaction), and the polymer was precipitated to obtain (3-alkylthiophene).
[0150] Dissolve benzothiazole acid in dichloromethane at a concentration of 0.05 mol / L. Mix the obtained benzothiazole acid dichloromethane solution with poly(3-alkylthiophene) (volume ratio of 1:1), and add an alkaline catalyst aqueous solution (such as NaOH aqueous solution), the concentration of the catalyst in the alkaline catalyst aqueous solution is 0.5 mol / L. The volume ratio of benzothiazole acid dichloromethane solution to poly(3-alkylthiophene) and alkaline catalyst aqueous solution is 10:10:1. The reaction temperature is 60°C and the time is 12h. After the reaction is completed, the product is washed with ethanol and precipitated to obtain poly(3-alkylthiophene) containing benzothiazole groups.
[0151] The poly(3-alkylthiophene) containing benzothiazolone groups was dissolved in ethyl acetate at a concentration of 5 mg / mL to obtain solution I. The mercaptoethanol aqueous solution was added to solution I (wherein the concentration of mercaptoethanol in the mercaptoethanol aqueous solution was 0.05 mol / L). The volume ratio of the mercaptoethanol aqueous solution to solution I was 1:10. The nucleophilic substitution reaction was carried out at 50°C. The reaction time was 4 hours. After the reaction was completed, precipitation was carried out. The side chain of the poly(3-alkylthiophene) was connected to the thiol group of the benzothiazolone group and dissolved in the ethyl acetate solution at a concentration of 3 mg / mL.
[0152] The polymer ethyl acetate solution is coated on the surface of the graphene conductive layer and dried at 80° C. for 1 h to form a self-repairing layer on the surface of the graphene conductive layer. The thickness of the self-repairing layer is about 200 nm, thereby obtaining Material I.
[0153] (VII) Take the material I prepared in this example, print silver paste electrodes on both ends of the graphene conductive layer using a 200 mesh screen, dry at 120°C for 1 hour, and form electrode sheets to obtain material II. The thickness of the electrode sheet is 20 μm; the area of the two electrode sheets on the surface of the graphene conductive layer can be 2-6%.
[0154] (VIII) Material II has an insulating layer (thickness 100-200 μm) encapsulated on the top and an overheat protection switch is added to make a near-infrared high-transmittance heating lens. Among them, a PTC (positive temperature coefficient) thermistor is used to obtain the overheat protection switch, and the PTC thermistor is made of a ceramic material (such as barium titanate). Electrode sheets are provided at both ends of the graphene conductive layer, and the electrode sheets are electrically connected to the graphene conductive layer.
[0155] This embodiment discloses a near-infrared high-transmittance heating lens (also called a near-infrared high-transmittance heating defog lens, the structural schematic diagram of which is shown in FIG. Figure 1As shown), comprising the composite conductive material prepared in this embodiment; wherein the area covered by the overheat protection switch and the electrode sheet in the lens is a non-transparent area, and the other areas are transparent areas; the transmittance of visible light in the transparent area of the heated lens is measured to be 5% to 6%, and the transmittance of near-infrared light with a wavelength of 800 to 1000 nm in the transparent area of the heated lens is 95%. Unless otherwise specified herein, the transmittance of the lens is the transmittance test result of the transparent area of the lens.
[0156] This embodiment discloses a near-infrared night vision device, including the near-infrared high-transmittance heated lens of this embodiment.
[0157] This embodiment discloses a near-infrared security monitoring lens, including the near-infrared high-transmittance heating lens of this embodiment.
[0158] Example 2
[0159] This embodiment discloses a composite conductive material, which differs from the embodiment 1 only in the preparation method of the graphene conductive layer. In this embodiment, the graphene conductive layer is prepared by a solvent stripping method. The steps of preparing the graphene conductive layer specifically include:
[0160] Highly oriented pyrolytic graphite is added to N-methylpyrrolidone solvent to form a 1 mg / mL graphite dispersion; the solution is ultrasonically treated by a probe ultrasonic machine at a power of 100 W for 10 hours; the ultrasonically treated solution is centrifuged (10000 RPM, 5 min); the supernatant is taken after centrifugation; a conductive layer is prepared by spin coating, and the polycarbonate substrate is spin-coated with the graphene solution (the above-mentioned supernatant) at a speed of 800 RPM for 10 seconds; and the graphene conductive layer is obtained by drying in a drying oven at 100° C. for 2 hours.
[0161] This embodiment discloses a near-infrared high-transmittance heating lens, which differs from Embodiment 1 only in the preparation method of the graphene conductive layer. In this embodiment, the graphene conductive layer is prepared by a solvent stripping method.
[0162] This embodiment discloses a near-infrared night vision device, including the near-infrared high-transmittance heated lens of this embodiment.
[0163] This embodiment discloses a near-infrared security monitoring lens, including the near-infrared high-transmittance heating lens of this embodiment.
[0164] Example 3
[0165] This embodiment discloses a composite conductive material, which differs from the embodiment 1 only in the preparation method of the graphene conductive layer. In this embodiment, the graphene conductive layer is prepared by a redox method. The steps of preparing the graphene conductive layer specifically include:
[0166] (I) Preparation of graphite oxide: In an ice bath, add 1g of graphite powder to 50mL of concentrated sulfuric acid and stir slowly to mix evenly. Slowly add a strong oxidant (3g of potassium permanganate) and control the addition rate to prevent the reaction from being too violent. Keep stirring for 2h in an ice bath, then heat the reaction system to 35°C and continue stirring for 10h. Slowly add 200mL of deionized water to the reaction system to dilute the reaction solution while controlling the temperature not to be too high. Add 3mL of 30% hydrogen peroxide solution by mass to reduce the excess oxidant and turn the reaction system bright yellow. Wash the product repeatedly with deionized water until the pH value of the washing solution is close to neutral. Then obtain graphite oxide by centrifugation (5000rpm, 3min), take the precipitate, and obtain graphite oxide.
[0167] (II) Preparation of graphene by reducing graphite oxide: Graphite oxide is dispersed in deionized water to form a graphite oxide dispersion with a concentration of 0.5 mg / mL. Dispersion is promoted by stirring for 1 hour. Hydroiodic acid, a reducing agent, is added, and the ratio of graphite oxide to hydroiodic acid is 1:10 (mass ratio). The reaction system is heated at 80°C for 5 hours to reduce graphite oxide to graphene. After the reaction is completed, the product is repeatedly washed with deionized water to remove residual reducing agent and impurities. Graphene is then obtained by centrifugation (5000rpm, 3min), and the precipitate is taken to obtain graphene.
[0168] (III) Preparation of graphene conductive layer: The prepared graphene was dispersed in water to form a graphene solution of 0.2 mg / mL. Ultrasonication was performed for 5 min using an ultrasonic device to uniformly disperse the graphene. The graphene solution was coated on a polycarbonate substrate by spin coating at a speed of 600 rpm for 10 s. The substrate was dried in a drying oven at 80° C. for 2 h to obtain a graphene conductive layer.
[0169] This embodiment discloses a near-infrared high-transmittance heating lens, which differs from Embodiment 1 only in the preparation method of the graphene conductive layer. In this embodiment, the graphene conductive layer is prepared by an oxidation-reduction method.
[0170] This embodiment discloses a near-infrared night vision device, including the near-infrared high-transmittance heated lens of this embodiment.
[0171] This embodiment discloses a near-infrared security monitoring lens, including the near-infrared high-transmittance heating lens of this embodiment.
[0172] Example 4
[0173] This embodiment discloses a composite conductive material, which is different from the embodiment 1 only in that this embodiment uses a copper substrate instead of the copper-nickel alloy substrate in the embodiment 1.
[0174] This embodiment discloses a near-infrared high-transmittance heating lens, which is different from the first embodiment only in that the copper-nickel alloy substrate in the first embodiment is replaced by a copper substrate in the first embodiment.
[0175] This embodiment discloses a near-infrared night vision device, including the near-infrared high-transmittance heated lens of this embodiment.
[0176] This embodiment discloses a near-infrared security monitoring lens, including the near-infrared high-transmittance heating lens of this embodiment.
[0177] Example 5
[0178] This embodiment discloses a composite conductive material, which is different from the embodiment 1 only in that this embodiment uses nickel foil to replace the copper-nickel alloy substrate in the embodiment 1.
[0179] This embodiment discloses a near-infrared high-transmittance heating lens, which is different from the first embodiment only in that the second embodiment uses nickel foil to replace the copper-nickel alloy substrate in the first embodiment.
[0180] This embodiment discloses a near-infrared night vision device, including the near-infrared high-transmittance heated lens of this embodiment.
[0181] This embodiment discloses a near-infrared security monitoring lens, including the near-infrared high-transmittance heating lens of this embodiment.
[0182] Comparative Example 1
[0183] This comparative example discloses a composite conductive material, which differs from Example 1 only in that this comparative example does not contain a photosensitive self-repairing layer.
[0184] This comparative example discloses a near-infrared high-transmittance heating lens, which is different from Example 1 only in that this comparative example does not contain a photosensitive self-repairing layer.
[0185] Test example
[0186] This test example conducted a performance test on the lens obtained in the embodiment, specifically including:
[0187] 1) The near-infrared high-transmittance heating lenses and intermediate materials prepared in each embodiment were tested. The test results are shown in Table 1.
[0188] Square resistance test: Turn on the four-probe square resistance tester and preheat it for 15 minutes, select the square resistance test mode, and place the film (substrate + graphene film) to be tested with the test surface (graphene film surface) facing up on the dedicated test platform of the tester. Use the four-probe probe to press on the conductive film, and make sure that the four probe heads are in good contact with the film. It is important to keep the distance from the edge of the probe to the edge of the material greater than the probe spacing (generally more than 10 times). Read the value and record the data.
[0189] Transmittance test of near-infrared high-transmittance heated lenses: Turn on the spectrophotometer, preheat the device for 15 minutes, calibrate the device, set the measurement wavelength range to 750-1100nm, start measuring, read the data, and record the transmittance value at a wavelength of 950nm.
[0190] Temperature measurement: At room temperature, a certain DC voltage (as shown in Table 1) is applied to the near-infrared high-transmittance heating lens, and the heating temperature of the near-infrared high-transmittance heating lens is tested using an infrared thermal imager, and the heating time t required to reach the set temperature (60°C) is recorded. When the set temperature is reached, the temperature difference within the heating surface is calculated as follows: (highest temperature within the surface - lowest temperature within the surface) / set temperature (60°C) * 100%; the highest temperature and the lowest temperature are selected using the 9-point test method: the average temperature is the average of the 9 temperature points in the figure below, as shown in the schematic diagram Figure 2 (T1 to T9 are temperature values, °C). The device under test is operated at the rated voltage (as shown in Table 1), and after the temperature rises to a stable state, the temperature values of the 9 points in the figure are measured in turn, and the temperature values of the 9 points are recorded. The arithmetic average of the temperatures of the 9 test points is taken as the set temperature of the heating device.
[0191] Defogging time: Install the near-infrared high-transmittance heating lens on glass or other test materials, put it in a refrigerator for 12 hours (the temperature in the refrigerator is 4°C), start the near-infrared high-transmittance heating lens for heating (the voltage shown in Table 1, the current passing through each lens is consistent), and record the time it takes for the fog to dissipate.
[0192] Weathering test:
[0193] 1) UV aging test: Place the sample in a UV aging box with a UV wavelength of 340nm and a power density of 0.5W / m 2 Monitor the sample appearance, transmittance (measurement wavelength 950nm), maximum temperature difference on the heating surface and line end resistance every 100 hours; test the sample performance after 1000 hours of UV aging: the transmittance drop of the near-infrared high-transmittance heating lens should not exceed 5% of the original transmittance, the change of the line end resistance value after the test should not exceed 2 times of the initial value, there is no obvious physical damage such as discoloration, blistering, cracks on the film surface, and the maximum temperature difference on the heating surface is less than 10%, which means the UV aging test is qualified.
[0194] 2) High and low temperature cycle test: Place the sample in a high and low temperature test chamber, heat the test chamber to 85°C at a rate of 10°C / min, keep warm for 30 minutes, then cool it to -40°C at a rate of 10°C / min, keep warm for 30 minutes. This is one cycle. After 100 cycles, test the sample performance: the transmittance of the near-infrared high-transmittance heating lens (measurement wavelength 950nm) should not decrease by more than 5% of the original transmittance, the change in the line end resistance value after the test should not exceed 2 times the initial value, there is no obvious physical damage such as discoloration, bubbling, cracks, etc. on the surface of the film, and the maximum temperature difference on the heating surface is less than 10%, which means the high and low temperature cycle test is qualified.
[0195] 3) Humidity resistance test: Place the sample in a constant temperature and humidity chamber, and apply the working voltage (as shown in Table 1), set the temperature of the constant temperature and humidity chamber to 85°C, and the humidity to 85% relative humidity. Monitor the sample appearance, transmittance (measurement wavelength 950nm), maximum temperature difference in the heating surface, and line end resistance every 100 hours; test the sample performance after 1000 hours of humidity resistance test: the transmittance of the near-infrared high-transmittance heating lens should not decrease by more than 5% of the original transmittance, and the change in the line end resistance value after the test should not exceed 2 times the initial value. There is no obvious physical damage such as discoloration, bubbling, cracks, etc. on the surface of the film, and the maximum temperature difference in the heating surface is less than 10%, which means that the humidity resistance test is qualified.
[0196] If the above three properties meet the requirements, the weather resistance test is qualified.
[0197] The near-infrared high-transmittance heating lens in Example 1 has a near-infrared light transmittance of more than 95%, a low heating voltage (5-12V), a high heating efficiency (reaching the set temperature in 30 seconds), a fast defogging speed (surface fog is removed within 60 seconds), and uniform heating of the entire surface (temperature difference is less than 6%). The effect of the lens after heating is shown in the figure below. Figure 3 shown.
[0198] Table 1
[0199]
[0200] As can be seen from the table above, the graphene prepared by CVD method has the highest purity, the best light transmittance and conductivity. The conductivity of graphene CVD method> solvent stripping method> oxidation-reduction method. The light transmittance of graphene CVD method> solvent stripping method> oxidation-reduction method. Therefore, the graphene conductive layer prepared by CVD method needs the lowest working voltage for heating and defogging lenses, the shortest defog time, and the most uniform heating surface temperature.
[0201] 2) When the graphene conductive layer in the heated defogging lens of the present invention is damaged (uneven heating or increased resistance at the end of the line), the photosensitive self-repair function of the damaged conductive layer can be activated. Repair method: Use ultraviolet light with a wavelength of 280 to 340 nm to irradiate the heated defogging lens in Example 1 with a power density of 0.2 to 5 W / cm 2 , irradiation time 3 to 30 minutes. The resistance of the conductive layer segment after repair decreased by 71%, heating recovery was uniform, and the transmittance changed little. Specifically:
[0202] The graphene conductive layer is judged damaged if it meets one of the following two criteria: 1. Resistance increase: If the resistance value at the end of the line rises to 2 times or more of the initial value, it is judged as damaged (due to the interruption or degradation of the conductive path, the flow of current is hindered and the resistance value increases); 2. Uneven heating: If the maximum temperature difference within the heating surface is ≥10%, it is judged as damaged due to uneven heating; the maximum temperature difference percentage within the surface = (highest temperature within the surface - lowest temperature within the surface) / set temperature);
[0203] The specific test results are shown in Table 2 below:
[0204] Table 2
[0205]
[0206]
[0207] 3) Statistics on the working time of the heated defogger lenses of Example 1 and Comparative Example 1, statistical method:
[0208] The working hours of the heated defogger lenses that have passed the test are counted. The test methods include: the near-infrared high-transmittance heated lenses are powered on and used in a high temperature and high humidity environment (85°C, 85% relative humidity) and a UV (340nm) irradiation environment. After heating to 60°C and 1000 hours, the surface is checked for obvious defects such as scratches, bubbles, cracks, deformation, stratification, impurities, etc. The transmittance change at 950nm is less than 5%; the maximum temperature difference within the heating surface is less than 10%; the line end resistance change is less than twice the initial value, which is qualified.
[0209] Place the qualified heated defogger lens (Example, Comparative Example 1) at room temperature and in a normal atmosphere (indoor or outdoor), apply a DC voltage (5V), heat to 60°C and maintain at 60°C, monitor the line end resistance, transmittance at 950nm and heating uniformity of the heated defogger lens every 100 hours: check that there are no obvious defects such as scratches, bubbles, cracks, deformations, stratification, impurities, etc. on the surface; the transmittance change is less than 5%; the maximum temperature difference within the heating surface is less than 10%; the line end resistance change is less than 2 times the initial value, which means normal operation, until any of the above items fails, and the working time is obtained by statistics. The test details are shown in Table 3:
[0210] Table 3
[0211] Experimental example Whether there is a repair layer Working hours / h loss / % Example 1 With repair layer ≥50000h <1% Comparative Example 1 No repair layer 32000h About 3%
[0212] The losses in Table 3 refer to the damage caused during the preparation or transportation of qualified products.
[0213] The working time of membrane products without repair layer is greater than 32,000 hours, and they cannot continue to work after the conductive layer is damaged. Membrane products with repair layer can self-repair after the conductive layer is damaged, extending the service life. Damage caused during product preparation or transportation can also be repaired through self-repair and can be used normally.
[0214] 4) The intermediate materials (polycarbonate substrate layer + graphene film) prepared in Examples 1 and 4-5 were subjected to the following performance tests (as shown in Table 4), wherein the reaction time refers to the deposition time required to deposit a graphene film of the same thickness as in Example 1:
[0215] Table 4
[0216]
[0217] The square resistance of the three substrates is slightly different. The graphene film prepared on the copper substrate has the highest transmittance and the longest reaction time, while the graphene film prepared on the nickel substrate has the lowest transmittance and the shortest reaction time. The reaction time of the copper-nickel alloy substrate is 50% less than that of the pure copper substrate, and the transmittance change is only 1%. The alloy substrate is preferred.
[0218] The near-infrared high-transmittance heating lens of the present invention uses graphene prepared by the CVD method as a conductive material, and has excellent properties such as high conductivity, high light transmittance, and high stability, which can improve the heating efficiency and near-infrared transmittance of the lens. And due to the uniform distribution and excellent conductivity of graphene, the heating layer of the lens can be evenly heated, avoiding the problem of uneven heating of traditional heating lenses. At the same time, the lens body adopts a near-infrared high-transmittance material, which further improves the infrared transmittance of the lens. And the conductive layer has a photosensitive self-repairing function after being damaged. Therefore, the near-infrared high-transmittance heating lens of the present invention has better performance in applications such as near-infrared night vision equipment and near-infrared security monitoring lens heating. In addition, the preparation method of the present invention is simple and feasible, and has the potential for large-scale production and promotion and application.
[0219] The present invention adopts a process method for preparing high-quality graphene film for near-infrared heating defogger lens by chemical vapor deposition, which is simple in process and low in cost, and can prepare large-area, high-quality graphene film. The conductive layer has a photosensitive self-repairing function.
[0220] If there is no special explanation, the actual meaning of "about" in the present invention is that the error is allowed within the range of ±2%, for example, about 100 is actually 100±2%×100. The "normal temperature" and "room temperature" in the present invention, if there is no special explanation, are about 20-30°C. The "between" in the present invention includes the number itself, for example, "between 2-3" includes the endpoint values 2 and 3.
[0221] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A composite conductive material, characterized in that: The invention comprises a near-infrared light-transmitting substrate and a graphene conductive layer arranged on the surface of the substrate, wherein the surface of the graphene conductive layer is provided with a photosensitive self-repairing layer capable of repairing the conductive layer.
2. The composite conductive material according to claim 1, characterized in that: The photosensitive self-repairing layer includes a conjugated polymer containing a benzothiazolone group and a thiol group.
3. The composite conductive material according to claim 1, characterized in that: The thickness of the photosensitive self-healing layer is 100-300nm; or / and, the thickness of the near-infrared transparent substrate is 120-250μm; or / and, the transmittance of near-infrared light in the near-infrared transparent substrate is 90-96%; or / and, the thickness of the graphene conductive layer is 0.5-5nm.
4. The composite conductive material according to claim 1, characterized in that: The composite conductive material further includes an electrode sheet, and the electrode sheet is electrically connected to the graphene conductive layer; or / and, the composite conductive material further includes an overheat protection switch.
5. A method for preparing a composite conductive material, characterized in that: The steps include: S1, preparing a graphene conductive layer; S2, compounding the graphene conductive layer with a near-infrared transparent substrate to obtain a material intermediate; S3, preparing a photosensitive self-healing layer on the side of the graphene conductive layer away from the near-infrared transparent substrate to obtain the composite conductive material.
6. The method for preparing a composite conductive material according to claim 5, characterized in that: In step S1, a graphene conductive layer is prepared by chemical vapor deposition.
7. A near-infrared high-transmittance heating lens, characterized in that: The composite conductive material comprises the composite conductive material according to any one of claims 1 to 4 or the composite conductive material prepared by the preparation method of claims 5 to 6.
8. Use of the composite conductive material according to any one of claims 1 to 4 or the composite conductive material prepared by the preparation method of claims 5 to 6 or the near-infrared high-transmittance heating lens according to claim 7 in night vision equipment or security monitoring equipment.
9. A near-infrared night vision device, characterized in that: The composite conductive material comprises the composite conductive material described in any one of claims 1 to 4 or the composite conductive material prepared by the preparation method of claims 5 to 6 or the near-infrared high-transmittance heating lens described in claim 7.
10. A near-infrared security monitoring lens, characterized in that: The composite conductive material comprises the composite conductive material described in any one of claims 1 to 4 or the composite conductive material prepared by the preparation method of claims 5 to 6 or the near-infrared high-transmittance heating lens described in claim 7.